The role of formative assessment in the Malaysian English language classroom: A case study / Adam Prakash Abdullah - Abdullah, Adam Prakash (2005)
The nature of formative assessment is still a fledging concept in the English Language classrooms in Malaysia. Educators, the public at large and the learners need to be fully aware of the many variables that influence assessments. Formative assessment is a comparatively new field in the Malaysian education system. The inclusion of project work in the Penilaian Menengah Rendah and the Sijil Pelajaran Malaysia examinations indicate that this method of assessment might figure more prominently in the Malaysian education system. This study aims to highlight the principles of formative assessment and its" practice in the Malaysian classroom. It is an essential case study as a big majority of teachers today are uninformed of the various test formats that they can utilize for and by themselves in the classroom. Using data derived from twenty five teachers from three secondary schools in the Klang Valley, this study examines their understanding of the parameters of formative assessment in their roles as teachers in the Malaysian English Language classroom. It also attempts to look at the use of formative assessment in the language classrooms and identify the factors that improve or hinder language learning. The findings revealed the following: The value of formative assessment has not been fully conceptualized in the present education system and there are still some gaps in the administration and implementation of formative assessment in Malaysian secondary schools. Teachers prefer 'teaching to the test' as they are concerned with face validity of a test. They are more concerned with tangible assessment methods that can be used to provide feedback to parents. Teachers choose more formal methods of assessment, particularly those that involve writing because it is more practical to carry out. The teacher can administer the test en masse to the students. The findings of this study established the fact that learners differ in many ways and these differences should be taken into considerations while planning the teaching and learning processes. Assessment should depict the true capabilities of the students thus achieving the purpose of formative assessment.